EKSPRESI SOSIAL YANG DIGUNAKAN OLEH MAHASISWA JURUSAN SASTRA INGGRIS DI KELAS DARING ANALISIS WACANA - Pratiwy, Olivia Natalia; Lasut, Theresia M.C; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT     This research entitled "Ekspresi Sosial yang Digunakan oleh Mahasiswa Jurusan Sastra Inggris di Kelas Daring Analisis Wacana". This research focuses on identifying and classifying the social expressions and the functions of social expressions, as well as analyzing and describing the language styles of English Department students in the Discourse Analysis online class. These expressions were used by studentsto respond the lecturer and communicate with theirfriends during the Discourse Analysis online class. The data were taken from 2 classes of Discourse Analysis via Zoom and Whatsapp group. This research uses theories of Kirkpatrick (2008) which aims to identify, classify, and the functions of social expressions; and Joss (1978) which aims to analyze and describe the language styles. To ensure the data collection process, the writer uses descriptive method. The results of this research shows that there only 10 of 30 types of social expressions, namely special greetings, greeting people, asking permission, giving thanks, giving warning, offering help, expressing uncertainty, apologizing, saying goodbye, and telling time and dates. The functions of social expressions that are used by the students, namely: the function of special greetings is a hope that the person is fine, successful, lucky, and so on; the function of greeting people as an informal alternative to hello! when you meetsomeone; the function of asking permission is you ask permission to do something; the function of giving thanks is a form of response to someone thanking you for something; the functions of giving warning is put up by someone who does not want other people going on their land without permission; the function of offering help is someone offers to help you with something; the function of expressing uncertainty when you do not know whether something is true or you have doubts about something; the function of apologizing is you wish to apologize to someone for something bad, unpleasant, inconvenient, etc that you have done; the function of say goodbye is you leave someone or when they leave you; and the function of tell times dan dates was you want to know the time. In terms of language styles, there are 4 of 5 levels of style that are used, those are: formal style, consultative style, casual or formal style, and intimate style. Formal style usually follows a commonly accepted format, impersonal and formal, there are 34 language styles of social expression used by English Department students in Discourse Analysis online class. Consultative style is used for someone to consult with someone, two or many people who have problem to consultancy. In this part, there are 6 language styles of social expression used by the students. Casual or informal style is used to communicate each other whether in chat or talking directly, there are 3 language styles of social expression used by the students in Discourse Analysis online class. Intimate style is used for closed people to get several information or others that are 2 secret with an intimate people. In this part, there are 13 language styles of social expression used by English Department students in Discourse Analysis online class.Key words: Social Expressions, English Department Students, Discourse Analysis Online Class